Experiments on the Effect of Kiln-seasoning of Planks from Three Species of Timber (Terminalia belerica, Terminalia tomentosa and Eugenia jambolana) as a Protection Against Insect Borers - Roonwal, M. L.; Chatterjee, P. N.; Thapa, R. S. (Indian Forester, 1956)
No abstract